Higher Intake of Dietary Magnesium Is Inversely Associated With COVID-19 Severity and Symptoms in Hospitalized Patients: A Cross-Sectional Study - Nouri-Majd, Saeedeh; Ebrahimzadeh, Armin; Mousavi, Seyed Mohammad; Zargarzadeh, Nikan; Eslami, Mina; Santos, Heitor O.; Taghizadeh, Mohsen; Milajerdi, Alireza (Frontiers in Nutrition, 2022)
Background and Aims Magnesium is an anti-inflammatory mineral that plays a role in the innate immune system, and the relaxation of bronchial smooth muscle warrants additional attention in COVID-19. This study examined the association between magnesium intake and COVID-19 severity and related symptoms in hospitalized patients. Methods A cross-sectional study was done enrolling 250 COVID-19 patients aged 18 to 65 years. A validated 168-item online food frequency questionnaire (FFQ) was used to assess dietary magnesium intake. COVID-19 Treatment Guidelines were used to determine COVID-19 severity, and symptoms were evaluated using a standard questionnaire. Crude and adjusted analyses were performed (Model 1: age, sex, and energy intake; Model 2: Model 1 + physical activity, supplements, corticosteroids, and antiviral drugs; Model 3: Model 2 + body mass index). Results The mean age of participants was 44.1 ± 12.1 years, and 46% of them had severe COVID-19. Patients at the highest tertile of dietary magnesium intake had lower serum levels of inflammatory biomarkers, including CRP (11.8 ± 2.2 vs. 29.5 ± 2.1 mg/L, p < 0.001) and ESR (15.8 ± 2.4 vs. 34.7 ± 2.4 mm/hr, p < 0.001), than those at the lowest tertile. After controlling for potential confounders, we observed that a higher dietary magnesium intake was associated with a lower odds of severe COVID-19 (OR: 0.32; 95% CI: 0.15–0.70). Also, we found a significant inverse association between dietary magnesium intake and odds of COVID-19 symptoms. Conclusion We found that higher intake of dietary magnesium was inversely associated with COVID-19 severity and symptoms.